Association of Intermittent and Constant Knee Pain Patterns With Knee Pain Severity and With Radiographic Knee Osteoarthritis Duration and Severity. Issue 6 (3rd June 2021) - Carlesso, Lisa C.; Hawker, Gillian A.; Torner, James; Lewis, Cora E.; Nevitt, Michael; Neogi, Tuhina; ,
Abstract : Objective: To examine the relation of knee pain patterns to pain severity and to radiographic osteoarthritis (OA) severity and duration. Methods: The Multicenter Osteoarthritis Study is a longitudinal cohort of older adults with or at risk of knee OA. Participants' Intermittent and Constant Osteoarthritis Pain (ICOAP) scores were characterized as 1) no intermittent or constant pain, 2) intermittent pain only, 3) constant pain only, and 4) a combination of constant and intermittent pain. Knee pain severity was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale and a visual analog scale (VAS). Radiographic knee OA (ROA) severity was defined as Kellgren/Lawrence grade ≥2, and ROA duration was defined according to the clinic visit at which ROA was first noted. We assessed the relation of ICOAP pain patterns to knee pain severity, ROA severity, and ROA duration using regression models with generalized estimating equations. Results: There were 2, 322 participants (mean age 68.8 years, body mass index 31.0 kg/m 2, 60% female). Higher ICOAP pain patterns, i.e., a mix of constant and intermittent pain, were associated with greater WOMAC pain severity compared with those patients without either pain pattern (odds ratio [OR] 43.2 [95% confidence interval (95% CI) 26.4–61.3]). Results were similar for the VAS (OR 71.2 [95% CI 45.7–110.9]). Those patients with more severe and longer duration of ROA were more likely to have a mix of constant and intermittent pain compared with those without either pain (OR 3.7 [95% CI 3.1–4.6] and OR 2.9 [95% CI 2.5–3.5], respectively). Conclusion: Knee pain patterns are associated with radiographic disease stage and duration, as well as pain severity, highlighting the fact that pain patterns are important for understanding symptomatic disease progression.